A Methods engineering study on Trinity Steel Products, Inc. - Arbis, Jenny Lyn L. (College of Engineering, 2001)
Trinity Steel Products, Inc. is a manufacturer of nails and other steel products such as galvanized wire, bolts, nuts, and other poleline hardware. This study focused only on the production of nails. Nails comprise the largest total output of the company, with 33.38% of the total sales. Although the steel wire used is also manufactured by Trinity steel, only nail operations will be discussed in this study . This study is limited by the observations the group made during the month of February 2001 and the data given by the company. The basis for analysis and discussion will be data gathered from observations, interviews, records and documents. Nail operations primarily involve the Marketing and Sales Division which dictates the amount and type of nails to be produced; the Production Control Division which monitors the amount and type of nails currently being produced; Quality Control which ensures the quality of nails delivered to customers; Nail Making Section which produces the rough nails; Tumbling Section produces the polished nails; and the Nail Packing Section which prepares the nails for ready delivery to customers. The group first conducted a thorough documentation to enable an accurate appraisal of the company's situation. The product, the process, and the system itself were properly documented to get a clear picture of the process of nail making. Problems observed and noted through interviews were listed down and analyzed one by one. The cause-and-effect relationships of the problems listed were also evaluated to identify the most critical problem. The problem found to be most significant due to its large damaging effect on production is the frequency in machine breakdown. Based on records, machine breakdown occurs at an average rate of 50 times a month for all 36 machines. Choosing the top six machines with the highest frequency of failure further restricted the analysis of machine breakdown. The six machines with the highest level of frequency of failure are as follow: Machine Type YT-03, Machine Type 3-S-01, Machine Type MC-C-01, Machine Type MC-F-02, Machine Type MTG-C-01 and Machine Type YT-04. Maintenance records of these six machines were gathered and tabulated to identify the most problematic parts of each machine. Pareto analysis was then conducted to identify the critical few parts that cause machine breakdown. Among the common critical parts are the grip lever, the side cutter, the die case, the nail catches, the side cam, and the slide hammer. The maintenance records were also used to identify the length of time needed to repair the machines. It was observed that most of the machine repairs and parts replacement could be done within the day. However, some machines have shown instances wherein the repairs took more than a month. Data such as these are important decision factors. These could be used in evaluating the alternatives suggested by the group in solving the company's problem. The purchase of new machines as replacement for the machines that are taking too long to repair was suggested by the group to bring back the company's level of production to its full potential. Maintenance improvement is also highly advisable due to the inevitable decline in the level of performance of the machines. The machines have been in operation for 20-50 years and continuous conditioning as a preventive measure should be taken.